2020
DOI: 10.1080/20008198.2019.1701778
|View full text |Cite
|
Sign up to set email alerts
|

The role of age and mode of delivery in the STEPS intervention: a longitudinal pilot-study in treatment of posttraumatic stress symptoms in Danish survivors of sexual assault

Abstract: Background: The STEPS programme has been succesfully implemented as a group-based treatment of trauma symptoms after rape for adolescents. The STEPS intervention was translated from Dutch to Danish and offered to adults in addition to adolescents as well as an individual intervention in addition to a group-based intervention at a Danish Centre for Rape Victims through 2011 to 2014. The programme was translated from Dutch to Danish and expanded to adults in addition to adolescents as well as to an individual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A recent systematic review on the global prevalence of sexual assault confirmed this reality: 27–44% of women, 11–25% of men, and 27–47% of transgender individuals experience sexual assault in their lifetime (Breiding et al, 2014 ; Dworkin, Krahé, & Zinzow, 2021 ; James et al, 2016 ; Langenderfer-Magruder, Eugene Walls, Kattari, Whitfield, & Ramos, 2016 Smith et al, 2018 ; Testa et al, 2012 ) with often significant mental health impact (e.g. Bach et al, 2021 ; Louison Vang, Ali, Christiansen, Dokkedahl, & Elklit, 2020 ; Villalta et al, 2020 ; Yeh et al, 2021 ). As the #MeToo movement clearly demonstrated, sexual assault is rarely perpetrated by strangers, by violent men pulling victims into the bushes, but instead most often by close friends, colleagues and family members.…”
Section: Sexual Violence From a Public Health Lensmentioning
confidence: 99%
“…A recent systematic review on the global prevalence of sexual assault confirmed this reality: 27–44% of women, 11–25% of men, and 27–47% of transgender individuals experience sexual assault in their lifetime (Breiding et al, 2014 ; Dworkin, Krahé, & Zinzow, 2021 ; James et al, 2016 ; Langenderfer-Magruder, Eugene Walls, Kattari, Whitfield, & Ramos, 2016 Smith et al, 2018 ; Testa et al, 2012 ) with often significant mental health impact (e.g. Bach et al, 2021 ; Louison Vang, Ali, Christiansen, Dokkedahl, & Elklit, 2020 ; Villalta et al, 2020 ; Yeh et al, 2021 ). As the #MeToo movement clearly demonstrated, sexual assault is rarely perpetrated by strangers, by violent men pulling victims into the bushes, but instead most often by close friends, colleagues and family members.…”
Section: Sexual Violence From a Public Health Lensmentioning
confidence: 99%
“…The involvement of Forensic Psychologists in an institution that has a team of forensic psychologists who are experienced and trained in supporting victims of crime in the process of recovery and protection (Louison Vang et al, 2020). Their inclusion in this research will provide valuable insights into best practices in helping rape victims.…”
Section: Introductionmentioning
confidence: 99%